Emotional Labor Dynamics: A Momentary Approach - Gabriel, Allison S.; Diefendorff, James M. (Academy of Management Journal, 2015)
Emotional labor has been described as a dynamic self-regulatory process that unfolds over the course of customer interactions, with employees continuously monitoring and adjusting their felt and expressed emotions via two emotion regulation strategies: surface acting and deep acting. Despite dynamic theory on the topic, empirical tests have largely ignored within-episode variability in emotional labor, relying on assessments of emotional labor focused on the person, day, or interaction level of analysis. The current study elaborated on theory pertaining to within-episode emotional labor dynamics, utilizing a call center simulation to examine how shifts in customer incivility impacted on continuous measures (captured every 200 milliseconds) of participants’ felt emotions, surface acting, deep acting, and vocal tone during a single interaction. Results provided evidence that customer behavior causally influences within-episode changes in emotions, emotion regulation, and vocal tone, and that these key emotional labor variables significantly relate to each other at the momentary level of analysis. Further, by modeling lagged effects, we were able to gain insight into the causal direction in the relationships among these continuously measured variables. Moreover, we showed for the first time that surface acting and deep acting are used simultaneously to manage emotional labor demands.